Criação de um parque tecnológico na cidade de Osório : proposta de um roteiro e sensibilização dos atores da tríplice hélice e da sociedade - Webber, Letícia Saltiél (Universidade do Vale do Rio dos Sinos, 2018)
The municipal development depends on factors that affect the ability to generate jobs and income, to increase their revenue and undertake investments. This problem involves various social forces as the Government, entities that promote knowledge, entrepreneurs and the society. With the intent to modify the environment in which one lives and assist the municipality of Osório/RS to find alternatives to alleviate local problems, idealized implementation of a technological park in the city. The city lacks a providing guidance for the implementation of the technology park, in this way, for the implementation of this initiative, the goal of this dissertation is to propose a roadmap indicating what the guidelines required for the creation of a park technology for the city of Osório and the form of awareness of the triple helix and actors of society. The proposal includes a script for procedures that must be performed to enable implementation of the Park, inspired by the model of governance of the triple helix. The achievement of the goals was possible through documentary research with exploratory qualitative approach, which allowed the access and analysis of data; the action research, which promoted the interaction of actors involved; and had the direction of the steps to the creation of the script as a Design Science Research with suggestions from Experts. This movement could be recorded in a field Notebook. With the survey, it was possible to observe that the municipality presents a regular development motivated principally by lack of investment and that it needs to increase employment and income, which decreased due to the decrease in production capacity and the aging of the population. Although the deployment of structuring technology-oriented technology park, with governance along the lines of the triple helix, would assist in local development, according to the suggestions of Experts. Thus, the proposed roadmap for the creation of the technological park has already achieved success since several steps have already been made proposals.
Keywords: Desenvolvimento; Parque Tecnológico; Roteiro; Tríplice Hélice; Sugestões de Experts; Development; Technological Park; Script; Triple Helix; Suggestions from Experts; ACCNPQ::Ciências Sociais Aplicadas::Administração